1989
DOI: 10.1002/1097-0142(19890215)63:4<791::aid-cncr2820630431>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer heterogeneity

Abstract: This study was carried out on 222 samples from 37 gastric carcinomas to assess the incidence of multiple stem lines in primary tumors and metastasis as reflected by multiple DNA stem lines and their relationship to epidermal growth factor (EGF) receptor expression, histologic grade, tumor size, and degree of wall infiltration. Fifteen primary tumors (40.5%) were homogeneously diploid/peridiploid whereas 22 (59.5%) were aneuploid. In the lymph node metastasis, seven patients (29.2%) had an homogeneous diploid/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 23 publications
1
11
0
1
Order By: Relevance
“…It has been reported that 33-40% of primary stomach cancers are heterogeneous in terms of tumour ploidy (Sasaki et al, 1988;De Aretxabala et al, 1989). Systematic investigation of the variation of SPF within primary stomach cancer has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 33-40% of primary stomach cancers are heterogeneous in terms of tumour ploidy (Sasaki et al, 1988;De Aretxabala et al, 1989). Systematic investigation of the variation of SPF within primary stomach cancer has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…One study found HER2 to have far lower levels of heterogeneity than other biomarkers studied, with c-myc and cyclinD1 exhibiting heterogeneity in 83 and 100% of samples, respectively. 28 In regards to tumor type, high levels of heterogeneity is well known in gastric carcinoma, 29 and one study found rates of intratumoral heterogeneity of KRAS mutations as high as 35-47% in colorectal tumors. 30 HER2 expression is generally far more heterogeneous in gastric carcinoma than in breast tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Only Yonemura et al (1990a) showed a signi®cant dierence in patient survival in relation to the Ki-67 labeling rate in an earlier study. These varying results might be due to a well-known fact: the great intratumoral heterogeneity of gastric carcinomas (De Aretxabala et al 1989). Most carcinomas consist of a heterogeneous population of tumor cells, within which there are dierent proliferation rates (Brown and Gatter 1990).…”
Section: Discussionmentioning
confidence: 99%